Meningkatkan Kreativitas Anak Usia Dini Melalui Metode Pembelajaran Loose Part - Farikhah, Aizatul; Mar’atin, Azkiyatul; Afifah, Lely Nur; Safitri, Riana Ayu (Institut Agama Islam Negeri Ponorogo, 2022)
The beginning of the use of the loose part method was due to the lack of children's ability to be creative in expressing ideas independently without the help of the teacher. This can be seen from the lack of children in completing skills in making a free work. Because learning is still glued to books, magazines or LKA. Loose part is known as a medium of teaching materials whose usefulness in children's learning is endless. The purpose of this research is that early childhood children in Muslimat NU Bunga Harapan Kindergarten have high creativity and are able to imagine using the items that have been provided. The number of research subjects was 48 students, each class consisted of 24 children. Research data was collected by means of observation, documentation, and interviews. The results of the loose part method show that the media can increase creativity in early childhood.